Feminist Resistance in Postcolonial African Narratives: Strategic Resistance and Radical Politics in Lola Shoneyin’s The Secret Lives of Baba Segi’s Wives and Chris Abani’s Becoming Abigail - Agyo, Azetu (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
This study investigates how African women navigate patriarchal oppression in Lola Shoneyin’s The Secret Lives of Baba Segi’s Wives and Chris Abani’s Becoming Abigail, with a particular focus on postcolonial subjectivity and feminist agency. It draws on two contrasting yet complementary theoretical frameworks: Snail-Sense Feminism, developed by Akachi Adimora-Ezeigbo, which champions strategic, non-confrontational forms of resistance; and Radical Feminism, which advocates for the complete dismantling of patriarchal systems. Shoneyin’s novel centres on subtle forms of resistance within a polygamous household in postcolonial Nigeria, while Abani’s novella highlights trauma, estrangement, and existential defiance in a more global, diasporic context. Employing a qualitative approach rooted in close textual analysis and feminist literary criticism, the research examines character development, narrative voice, and recurring motifs such as silence, memory, and resistance. The analysis reveals that female characters in both texts adopt layered strategies of survival—from covert manipulation and collective solidarity, as exemplified in Iya Segi’s domestic politics, to acts of epistemic refusal and bodily autonomy, seen in Abigail’s final gesture of resistance. This study contributes to postcolonial feminist discourse by emphasising the diversity and complexity of African women’s agency, shaped by the intersecting forces of tradition, modernity, and colonial legacies. It argues that resistance in African literature is neither uniform nor solely radical, but rather emerges through contextually embedded acts of endurance, negotiation, and redefinition. Ultimately, both texts offer valuable insights into the lived experiences of African women, portraying feminist agency not as a single path but as a constellation of adaptive—and at times contradictory—responses to patriarchal and postcolonial realities.